2016
DOI: 10.1007/s12686-016-0550-y
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater vertebrate metabarcoding on Illumina platforms using double-indexed primers of the mitochondrial 16S rRNA gene

Abstract: Purpose -The purpose of this paper is to propose a framework integrating the Hart and Milstein (2003) strategies for organizational sustainable development (SD) with the ideas of Kleindorfer et al.(2005) on sustainable operations management (SOM), which requires guidance of green supply chain management (GSCM). Design/methodology/approach -The construction of the framework was based on previous studies that discussed synergies between operations management principles with environmental bias and studies on adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 76 publications
(101 reference statements)
2
39
0
Order By: Relevance
“…Most prior eDNA studies have examined vertebrates in temperate freshwater streams [66], lakes [67] or sea water [68,69]. However, Lopes et al [30] recently demonstrated that eDNA surveys were effective in revealing anurans in streams in the Brazilian Atlantic forest, while Robson et al [32] developed eDNA protocols that employ qPCR to detect invasive fish in tropical environments.…”
Section: Discussionmentioning
confidence: 99%
“…Most prior eDNA studies have examined vertebrates in temperate freshwater streams [66], lakes [67] or sea water [68,69]. However, Lopes et al [30] recently demonstrated that eDNA surveys were effective in revealing anurans in streams in the Brazilian Atlantic forest, while Robson et al [32] developed eDNA protocols that employ qPCR to detect invasive fish in tropical environments.…”
Section: Discussionmentioning
confidence: 99%
“…Most prior eDNA studies have examined vertebrates in temperate freshwater streams [63], lakes [64] or sea water [65,66]. However, Lopes et al [30] recently demonstrated that eDNA surveys were effective in revealing anurans in streams in the Brazilian Atlantic forest, while Robson et al [32] developed eDNA protocols that employ qPCR to detect invasive fish in tropical environments.…”
Section: Discussionmentioning
confidence: 99%
“…There are three major approaches for of eDNA detection: the use of qPCR to detect one or a small number of target species [67,68], shotgun sequencing of aquatic metagenomes [69] and PCR-based metabarcoding [28,29,6366]. Metabarcoding studies cannot deliver information on species composition without a reliable reference database, such as that available for Mexican freshwater fishes which includes records for 93% of the 70 species known from Lake Bacalar and associated wetlands [48,51–54,70].…”
Section: Discussionmentioning
confidence: 99%
“…16S rRNA is a mitochondrial gene, present in higher copy number than nuclear genes in eDNA samples (Thomsen & Willerslev, ). It does not show great variation within species, but it shows high variation between closely related species, especially in fishes (Maretto, Reffo, Dalvit, Barcaccia, & Mantovani, ; Vences et al, ). The number of sequences for fishes in databases is similar to other mitochondrial genes such as cytochrome c oxidase subunit 1 ( COI ) or cytochrome b (Machida, Leray, Ho, & Knowlton, ).…”
Section: Methodsmentioning
confidence: 99%